2003
DOI: 10.1016/s0886-3350(02)01534-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a capsular tension ring for phacoemulsification in eyes with zonular dialysis

Abstract: Phacoemulsification with in-the-bag PC IOL and CTR implantation in eyes with zonular dialysis of up to approximately 150 degrees had a success rate of 90.47%. Visual recovery was not as good as in normal eyes because of the problems associated with zonular dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 16 publications
4
59
0
12
Order By: Relevance
“…This is similar to the finding of Jacob S et al, who studied 21 eyes and calculated best corrected visual acuity to be ≥6/12 which was achieved in 71.42% patients [13] Studies by Ma X et al, and Vasavada AR et al, have also reported improved BCVA in 91.7% and 85.4% patients respectively [14,19]. Only 6 (13.33%) patients in our study had achieved visual acuity ≤6/60 which was due of pre existing fundus pathology.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This is similar to the finding of Jacob S et al, who studied 21 eyes and calculated best corrected visual acuity to be ≥6/12 which was achieved in 71.42% patients [13] Studies by Ma X et al, and Vasavada AR et al, have also reported improved BCVA in 91.7% and 85.4% patients respectively [14,19]. Only 6 (13.33%) patients in our study had achieved visual acuity ≤6/60 which was due of pre existing fundus pathology.…”
Section: Methodssupporting
confidence: 91%
“…However among 21 eyes investigated by Jacob S et al, showed iritis in 23.8% and keratitis in only 9.28% patients [13]. Higher incidence of immediate postoperative keratitis seen in our patients can be attributed to probable higher percentage of patients with hypermature cataract and pseudoexfoliation syndrome.…”
Section: Methodsmentioning
confidence: 40%
“…13 A prospective study of 21 eyes from 19 patients, with documented zonular dialysis and CTR use, showed that 15 eyes (74.42%) had a postoperative BCVA of 6/12 or better. 13 Similarly, a study by Ionides et al 14 assessed BCVA in 17 patients with zonular dialysis, and found an acuity of 6/12 or better in 80% of patients with no previous ocular co-morbidity, and in 42.9% of patients with ocular co-morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Zonular weakness is often described according to the number of clock hours, which reflect the degree of zonular dialysis [13][14][15]. However, a more simplified system that more easily grades zonule quality is needed (i.e., using 0 for some grades).…”
Section: Discussionmentioning
confidence: 99%